Factors Influencing Consumer Intention to Purchase Online: A Study Among Female Consumer in Johor, Malaysia - Ramli, Norshazliza; Rashid, Umi Kartini; Nasuredin, Juzaimi; Kepal, Noreina (Research in Management of Technology and Business, 2021)
In Malaysia, despite the fact that the awareness of online shopping is rising its popularity and growing rapidly, yet the studies on factors that influence online purchase intention among female Malaysian consumers are still lacking. In other cases, some of the researchers even claimed that online shopping among Malaysian is still at the infant stage and the potential for its growth is inevitable. This study investigated the applicability of the Theory of Planned Behaviour (TPB) in predicting the female Malaysian consumers on their intention towards online purchasing. The research intended to investigate the influencing factors of attitude, subjective norm and perceived behavioural control towards online purchase intention among female consumers in Johor. The target respondents in this study were Malaysian female who are aged 15 years old and above. A quantitative study was conducted and for data collection, an online questionnaire was distributed to 384 individuals through online.